Prevention of Unnoticed Deterioration And Improvement In Outcome of Critically Ill Patients By Implementation of National Early Warning Score 2 In A High Dependency Unit In Bangladesh: A Quality Improvement Project (Bangladesh Journal of Medicine, 2023)
This Quality Improvement Project (QIP) was aimed to assess the acceptability and utility of the National Early Warning Score 2 (NEWS2) in a Bangladeshi level-2 care setting.All nurses and physicians were trained on NEWS2 scores and proper response before starting the QIP. Utilization of NEWS2 and patient outcome were documented and analyzed. Acceptability was recognized by increase in utilization, and utility by reduction in unnoticed deterioration of patients. With modified NEWS2 chart, it became well adopted and utilized by the nurses. Data from 3828 patients showed statistically significant reduction in unnoticed deterioration evident by lowering of sudden cardiac arrest and ICU transfer (0.35% vs 2.6% and 2.33% vs 6.6%, p=